Local Wisdom of Customary Law Community to Realize Food Sovereignty in Central Sulawesi - Miqat, Nurul; Nur, Rafika; Fattah, Virgayani; Sulilawati, Susi; Purnamasari, Intan (Universitas Negeri Gorontalo, 2021)
Indigenous peoples have the right to food sovereignty, the right of indigenous peoples to meet food needs following local wisdom owned by indigenous peoples following their potential resources and culture, produced independently with their systems. Food production systems follow the conditions of traditional territories, traditional values / norms and knowledge of indigenous peoples, agricultural systems, trade, fisheries, and other production systems in traditional territories. Central Sulawesi, as one of the provinces that still has several areas, which are indigenous community areas, has local wisdom in terms of food security. The availability of food based on the independence of an area cannot be separated from the efforts of the community to maintain regional food security in a way that has become the standard of behavior of the surrounding community in managing the environment that can produce quality food, one of which is the standard of community behavior which is reflected in local wisdom. Through local wisdom in managing the environment, it is hoped that it will be a concrete step to strengthen it carrying capacity, especially in the food aspect. Through Law No. 18 of 2012, which seeks to give obligations to the state to respect, fulfill and protect the right to food of the Indonesian people without exception.